Organizacja systemu budżetowania w stacji radiowej - Kotapski, Roman (The Organization of Budgeting System at a Broadcasting Radio Station., 2006)
If the board of directors wants to put into practice the budgeting system they must give aims of this systems. The elements of this budgeting system are budgets, budgets' regulations, accounting system, budgeting system of control, budgeting computer system. The budgeting system of the radio station and an estimated cost of broadcasting are described.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1101, s. 108-115